Forestry and the Forest Industry in Japan - Iwai, Yoshiya, 1945- (Book collections on Project MUSE., 2002)
In recent years, Japan, like many other forest-dependent nations, has been facing difficult times: forest self-sufficiency is low; unplanted areas after harvesting are increasing; and forest industries and companies are losing international competitiveness in the global market. Such challenges, however, are not unique to Japan but are relevant - and all too familiar - to forest industry stakeholders around the world. This book, representing the work of distinguished Japanese scholars, is the first comprehensive English-language overview of forestry, forest management, and the forest products industry in Japan. Chapters address the biological and physical evolution of the forest, forest-dependent industries, the social impact of changes in forest utilization, current trends in the forest estate, and the relationship between urban population and rural forest land. Forestry and the Forest Industry in Japan will be welcomed by scholars, students, and policy makers in the areas of forest policy, international trade, international forestry, and forest products marketing.